2015
DOI: 10.1186/s12889-015-2098-2
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of HIV, viral hepatitis and STI prevention needs among African migrants in Germany; a cross-sectional survey on knowledge, attitudes, behaviors and practices

Abstract: BackgroundMigrants from sub-Saharan Africa (MisSA) are a relevant sub-group for HIV-transmission in Germany. A total of 10-15 % of all newly diagnosed cases are MisSA, and approximately one third acquired HIV in Germany. There is limited information on knowledge, attitudes, behaviors and practices (KABP) regarding sexual health in African communities residing in Germany.MethodsFrom October-December 2013 we conducted a cross-sectional survey on KABP regarding HIV, viral hepatitis (HEP), and sexually transmitted… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
19
1
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 23 publications
2
19
1
1
Order By: Relevance
“…Peer researchers recruited 649 study participants within 2 months and overexceeded our aimed sample size of 350 MisSA. Working with peer researchers enabled us to reach particularly vulnerable groups, such as persons without health insurance (22% of participants) [44,45]. …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Peer researchers recruited 649 study participants within 2 months and overexceeded our aimed sample size of 350 MisSA. Working with peer researchers enabled us to reach particularly vulnerable groups, such as persons without health insurance (22% of participants) [44,45]. …”
Section: Discussionmentioning
confidence: 99%
“…The study design was developed as a CBPHR project with persons working in HIV/STI prevention with MisSA, key persons from MisSA communities, and HIV/STI researchers; we conducted a pilot study to test feasibility of the study design in Hamburg before finalizing the study flow. Details on the description of the research process and the pilot study can be found elsewhere [44,45]. …”
Section: Methodsmentioning
confidence: 99%
“…Results of participatory research at the Robert Koch Institute among migrants from Sub-Saharan Africa in Germany (MiSSA) show that migrants of this group were often not aware of the anonymous and free HIV-testing offer or assumed that a positive HIV-test will impact their legal status in the country [24]. These together with the fear of stigmatization of HIV-positive migrants in their communities have constituted barriers to HIV testing in African migrants in the past [22, 25–28].…”
Section: Discussionmentioning
confidence: 99%
“…To determine risk of acquiring STIs among other behaviours, each participant completed a self-guided Knowledge Attitude Behaviour and Perception (KABP) questionnaire. KABP questionnaires are commonly used in research to identify information related to sexual behaviours and stigmas associated with STIs (16,17). The KABP questionnaire used in this project was a modified version of the assessment administered to conscripts in 2012 (18).…”
Section: Methodsmentioning
confidence: 99%